Visualization techniques in agriculture - Ragán, Péter; Bakó, Károly; Dövényi-Nagy, Tamás (Acta Agraria Debreceniensis, 2014)
This paper describes a dynamic map representation method which provides a flexible, spectacular and cost-effective opportunity for the illustration and description of spatial data due to its parametrability, web-based publication and the free sowftare it uses in multi-user circumstances. The tasks of the database serves and the processing were performed by an ASUS WL-500 G Premium v2 router and a 80 GB hard disk. The database contains the measured data of the nitrogen fertilisation experiment established on the Látókép Experiment Site of the Centre for Agricultural Sciences of the University of Debrecen. The tests showed that the generation time of the processor which was run through the router did not significantly increase. Therefore, the configuration developed by us is suitable for users who do not wish to invest into a large and expensive server, but they still want to view their data quickly and easily, as well as to reach them from anywhere. The available data were not sorted into a database which was performed with Quantum GIS in a way to have an optimum database structure which is adjusted to the expected areas of use and the expected running speeds were also taken into consideration. The processor which processes the database items was written in PHP language. The main role of the processor is that it produces a KML file real time which is suitable for viewing with a given map viewer client (e.g. Google Earth). This application makes it possible to view information related to geographical objects, values stored in the database or those calculated by the processor on a map in 2D or 3D in a versatile way.